2019
DOI: 10.1038/s41598-019-42502-5
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of bacteremia by exploiting host-pathogen interactions of lipoteichoic acid and lipopolysaccharide

Abstract: Bacteremia is a leading cause of death in sub-Saharan Africa where childhood mortality rates are the highest in the world. The early diagnosis of bacteremia and initiation of treatment saves lives, especially in high-disease burden areas. However, diagnosing bacteremia is challenging for clinicians, especially in children presenting with co-infections such as malaria and HIV. There is an urgent need for a rapid method for detecting bacteremia in pediatric patients with co-morbidities to inform treatment. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 63 publications
(93 reference statements)
0
27
0
3
Order By: Relevance
“…Previous work from our group has demonstrated that LAM is associated with high-density lipoproteins (HDL) in host blood [ 45 ]. This association should be considered when developing diagnostics, as with membrane insertion and lipoprotein capture methodologies [ 43 , 137 , 141 , 142 , 143 , 144 ], because traditional strategies for measuring the monomeric antigen are likely to be unsuccessful in this conformation. To date there are only a few studies showing detection of LAM in blood from adults [ 46 , 47 , 133 ] and none in a pediatric population.…”
Section: The Role Of “Omics” In Tb Diagnostic Developmentmentioning
confidence: 99%
“…Previous work from our group has demonstrated that LAM is associated with high-density lipoproteins (HDL) in host blood [ 45 ]. This association should be considered when developing diagnostics, as with membrane insertion and lipoprotein capture methodologies [ 43 , 137 , 141 , 142 , 143 , 144 ], because traditional strategies for measuring the monomeric antigen are likely to be unsuccessful in this conformation. To date there are only a few studies showing detection of LAM in blood from adults [ 46 , 47 , 133 ] and none in a pediatric population.…”
Section: The Role Of “Omics” In Tb Diagnostic Developmentmentioning
confidence: 99%
“…Because of this sequestration, it is necessary to liberate the amphiphilic biomarkers from their lipoprotein carriers in order to enable sensitive measurement. Detection can then occur via enzyme-linked immunosorbent assays (ELISA’s), waveguide-based biosensors 5 , 6 , 8 , 10 , or other methods 9 .…”
Section: Introductionmentioning
confidence: 99%
“…This article is a US Government work. It is not subject to copyright under 17 USC The copyright holder for this preprint this version posted November 20, 2020. ; https://doi.org/10.1101/2020.11.20.391037 doi: bioRxiv preprint 7 directly captures LAM based on its thermodynamic propensity for association with a supported lipid membrane which forms the functional surface of a biosensor (22,24,25). Although both of these assays are platform ambivalent, we used enzyme linked immunosorbent assays (ELISA) and fluorescence measurements from a waveguide-based biosensor platform developed at the Los Alamos National Laboratory for this study (19,26).…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the impact of serum sequestration of LAM in host lipoprotein complexes, we measured serum LAM using two methods tailored for the detection of amphiphilic biomarkers in aqueous matrices (Figure 1) – lipoprotein capture and membrane insertion. The lipoprotein capture assay (Figure 1) relies on capture of host lipoproteins, exploiting their biological association with the pathogen amphiphile to “concentrate” LAM (19,24). In contrast, the membrane insertion assay (Figure 1) is independent of that host lipoprotein/LAM association, and directly captures LAM based on its thermodynamic propensity for association with a supported lipid membrane which forms the functional surface of a biosensor (22,24,25).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation